Experimental study on mechanical properties and failure modes of low-strength rock samples containing different fissures under uniaxial compression. (15th June 2018) - Wang, Yanlei; Tang, Jianxin; Dai, Zhangyin; Yi, Ting
Highlights: Specimen material belong to low-strength rock masses. The influence of fissures on low-strength rock mass is distinguished from that of high-strength rock masses. The failure of ductile flow deformation occurs in the post-peak failure stage. UCS, axial peak strain and elastic modulus are most sensitive to the fissure dip angle and fissure number. Fissure dip angle can completely change the failure mode of low-strength rock specimens. Abstract: Uniaxial compressive tests (UCS) were carried out to investigate the influence of pre-existing fissure geometry parameters (various dip angles, lengths, widths, and numbers) on the mechanical properties and deformation failure modes of low-strength rock samples. The results suggested that UCS, elastic modulus and axial peak strain were reduced by pre-existing fissures, but the reduction degree was strongly associated with the pre-existing fissure geometry. In addition, the UCS and elastic modulus of the low-strength rock samples were very sensitive to fissure dip angle and number, while the fissure number had the greatest effect on both of them. The axial peak strain was mainly influenced by the fissure dip angle. Moreover, due to the influence by the pre-existing fissures, the stress-strain curves of low-strength rock specimens usually changed from rapid drop to multistage decline, and even to horizontal extension slow decline. This indicated that low-strength specimens usually can change from brittle failure to ductile failure, and even had ductile flow deformation damage occurring under the influence of the pre-existing fissures. This change did not occur in high-strength rock mass. The fracture morphology of low-strength rock specimens was primarily affected by the fissure dip angle, and the influence of the fissure number on the fracture morphology was constrained by the fissure dip conditions, while the fissure length and width had fairly little effects on the fracture morphology of low-strength rock samples. This paper may provide new insights into the principle features of rock failure under uniaxial compression for future studies.